Does spatial awareness training affect anatomy learning in medical students?. Issue 6 (10th March 2020) - Gonzales, Rene A.; Ferns, Gordon; Vorstenbosch, Marc A. T. M.; Smith, Claire F.
Abstract : Spatial ability (SA) is the cognitive capacity to understand and mentally manipulate concepts of objects, remembering relationships among their parts and those of their surroundings. Spatial ability provides a learning advantage in science and may be useful in anatomy and technical skills in health care. This study aimed to assess the relationship between SA and anatomy scores in first‐ and second‐year medical students. The training sessions focused on the analysis of the spatial component of objects' structure and their interaction as applied to medicine; SA was tested using the Visualization of Rotation (ROT) test. The intervention group ( n  = 29) received training and their pre‐ and post‐training scores for the SA tests were compared to a control group ( n  = 75). Both groups improved their mean scores in the follow‐up SA test ( P  < 0.010). There was no significant difference in SA scores between the groups for either SA test ( P =  0.31, P =  0.90). The SA scores for female students were significantly lower than for male students, both at baseline and follow‐up ( P  < 0.010). Anatomy training and assessment were administered by the anatomy department of the medical school, and examination scores were not significantly different between the two groups post‐intervention ( P =  0.33). However, participants with scores in the bottom quartile for SA performed worse in the anatomy questions ( P  < 0.001). Spatial awareness training did not improve SA or anatomy scores; however, SA may identify students who may benefit from additional academic support.